Rethinking Catatonia: New Insights from the Autism Spectrum - Dell’Osso, Liliana; Toschi, Daniela; Amatori, Giulia; Gesi, Camilla (CNS & Neurological Disorders - Drug Targets, 2023)
Initially conceptualized as a subtype of schizophrenia, catatonia has progressively been recognized to occur in a wide variety of conditions as a kind of final common pathway for many severe mental disorders. There is a significant overlap between the fundamental symptoms of autism spectrum disorder (ASD) and catatonia, and ASD can frequently complicate catatonic states. While provocative, the hypothesis that neuroatypicality may represent the submerged structural piece underlying catatonic states is intriguing. Yet, the multifaced relationship between catatonia and ASD may provide new insights into the etiology and treatment of both disorders.
Keywords: DSM-5